Status Vitamin D pada Remaja Sehat Usia 15-18 Tahun di Kota Depok - Dyah Saptarini (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2019)
Introduction: Vitamin D is a nutrient whose main source is obtained from sunexposure. It is estimated that 1 billion of the world’s population from variousethnicities and age groups experience vitamin D deficiency (vitamin D defi-ciency = VDD). Research on vitamin D in adolescents is still limited in Indo-nesia.Objective: Knowing the vitamin D status of healthy adolescent communities inDepok City aged 15-18 years, and related factors, including nutritional status,vitamin D intake, fat and sun exposure scores. Method: Cross-sectional study with 60 subjects. Examination of vitamin Dlevels using the Direct Competitive Chemiluminescence Immunoassay (CLIA)method. Subject nutritional status based on the CDC 2000 IMT / Age chart.Sun exposure scores using the Sun Exposure Scoring by Hanwell et al. Assess-ment of vitamin D and fat intake with semiquantitative and 24 hours food recallFFQ. Results: The average value of vitamin D and vitamin D intake was 17.29±6.77ng/ml and 5.47±3.96 μg/day respectively. Middle BMI 19.67(14.22-36.98)kg/m2.Sun exposure 11 (4-42) and fat intake 42.1 (8.75-1 -, 58)g/day. Conclusion: Vitamin D status of the subject, healthy adolescents, showed in-sufficiency, with normal nutritional status.